2013
DOI: 10.1021/om400407p
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Crystal Model for MgCl2–Electron Donor Support Materials: [Mg3Cl5(THF)4Bu]2 (Bu = n-Butyl)

Abstract: The influence of the electron donor tetrahydrofuran (THF) on the formation of the crystalline morphology of MgCl 2 was studied. MgCl 2 was synthesized from magnesium and 1-chlorobutane in the presence of THF with the THF/Mg molar ratio ranging from 0.063 to 2.0. With the highest amounts of THF crystalline particles were formed, as evidenced from scanning electron microscopy images. The X-ray structure analysis of these single crystals revealed the new organometallic Mg compound [Mg 3 Cl 5 (THF) 4 Bu] 2 (Bu = n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…5,7,8,[29][30][31] In our previous works we have demonstrated the potential of a multi-technique approach in unraveling the nature of the active TiCl x phase in catalysts obtained by reacting together titanium and magnesium chloride tetrahydrofuranate precursors and the aluminum-alkyl activator. 7,8 The investigation is more complex when the TiCl x and MgCl x phases are simultaneously supported on dehydroxylated silica in presence of tetrahydrofuran.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8,[29][30][31] In our previous works we have demonstrated the potential of a multi-technique approach in unraveling the nature of the active TiCl x phase in catalysts obtained by reacting together titanium and magnesium chloride tetrahydrofuranate precursors and the aluminum-alkyl activator. 7,8 The investigation is more complex when the TiCl x and MgCl x phases are simultaneously supported on dehydroxylated silica in presence of tetrahydrofuran.…”
Section: Introductionmentioning
confidence: 99%
“…The support was synthesized as described previously in the literature [27]. Autoclave was packed with Mg (0.5 g, 0.021 mol), few small crystals of iodine, octane (20 mL), 1-chlorobutane (4.6 mL, 0.044 mol), and THF (0.005 or 0.041 mol).…”
Section: Synthesis Of Supports and Catalystsmentioning
confidence: 99%
“…In our previous study [27], the effect of THF on the morphology and the structure of synthesized MgCl 2 were studied. It was found that a transition from a fully crystalline to structurally disordered complexes can be controlled by adjusting the amount of THF in the autoclave synthesis of MgCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to its easiness to prepare, which leads to the lower in cost. It also provides good hydrogen response and the moderate activity and increases the molecular weight of polymer [4][5][6]. Besides, Sobota [7] revealed that THF is the most mature as a selectivity control agent in ethylene polymerization.…”
Section: Introductionmentioning
confidence: 99%